Higher Order Thinking Skills Used By English Teachers in Designing Test Items at SMAN Argamakmur - Bilqisty Alghifari; Eki Saputra; Waslurachim Safitri; Yupika Maryansyah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Test items or questions play an important role as a tool to measure the students’ ability in a process, like the process of education and learning. The objectives of this research are to find out the kinds of higher order thinking skill used by English teachers and to find out the dominant kinds of higher order thinking skill used by English teachers in designing test items at SMAN Argamakmur. This study used descriptive study which tries to potrait the use of Higher Order Thinking Skills in designing test items. This research used test items designed by English teachers in SMAN Argamakmur. The researcher asked permission to the teachers to copy the latest test items. The instruments of this research was observation checklist. In collecting the data, the researcher used the composition of higher order tinking skills. The data was collected based on the reading task on the test items designed by English teachers. There were two conclusions of this research; firts, the kinds of higher order thinking skill used by English teachers in designing test items at SMAN Argamakmur were analyzing, evaluating, and creating. Second, the dominant kind of higher order thinking skill used by English teachers in designing test items at SMAN Argamakmur was analyzing. Keywords : Higher Order Thinking Skills, Test Items